1986
DOI: 10.1002/btpr.5420020405
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Angle Neutron Scattering Studies of Protein‐Reversed Micelle Complexes

Abstract: Enzymes solubilized in organic solvents, hosted within the polar cores of surfactant aggregates, known as reversed micelles, provide many unique opportunities for new biocatalytic synthesis and protein separation processes. Small-angle neutron scattering (SANS) studies have shown that insertion of the protein cytochrome-c in the reversed micelle polar core causes a significant reapportioning of the surfactants and water between the filled and unfilled micelles, leading to an increase in overall size of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…As for both trioctylmethylammonium chloride and AOT a similar intercept is found, one would expect that the size of the reversed micelles is comparable. This is however unlikely, as AOT micelles have, under the experimental conditions used, a M', of about 15 [42], whereas trioctylmethylammonium chloride reversed micelles have a w, of 6 under the experimental conditions used. For trioctylmethylammonium chloride micelles a smaller radius is expected but no data are available.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As for both trioctylmethylammonium chloride and AOT a similar intercept is found, one would expect that the size of the reversed micelles is comparable. This is however unlikely, as AOT micelles have, under the experimental conditions used, a M', of about 15 [42], whereas trioctylmethylammonium chloride reversed micelles have a w, of 6 under the experimental conditions used. For trioctylmethylammonium chloride micelles a smaller radius is expected but no data are available.…”
Section: Resultsmentioning
confidence: 95%
“…Above, we interpreted the intercept as the maximal M , that can be incorporated into reversed micelles without an increase in micellar size. Sheu et al [42] demonstrated that the radii of filled and empty reversed AOT micelles, prepared by extraction of cytochrome c from a 0.1 M KCl solution are 4.57 nm and 4.61 nm, respectively. As for both trioctylmethylammonium chloride and AOT a similar intercept is found, one would expect that the size of the reversed micelles is comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Models proposed in the literature for reverse micelles characterization range from simple geometric models (22)(23)(24)(25)(26) to more rigorous molecular thermodynamic models (27)(28)(29). Several experimental methods and empirical models have been employed to determine the size and shape of reverse micellar aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…ls718 The knowledge of the geometrical parameters of the microemulsion particles and their size distribution is very important to correctly interpret the observed phenomena and to develop good theoretical models of the driving forces responsible for both droplet formation and polymer and biopolymer solubilization in micro emulsion^.^-^^ In the last years these problems were often discussed and a number of experimental studies and theoretical models have been presented. [12][13][14][15][16][17][18][19] However, no unambiguous solution to these problems has been found, and the situation still remains controversial. It is the aim of this study to show that we can use dynamic (DLS) and static (SLS) light scattering experiments close to the so-called optical match point as a very sensitive method20 to quantitatively test the currently existing theories for the formation of microemulsion droplets on the one hand and for the protein solubilization in microemulsions on the other hand.…”
Section: Introductionmentioning
confidence: 99%